A PROSPECTIVE STUDY OF DRUG UTILIZATION PATTERN OF ANTI-EPILEPTIC DRUGS AND THEIR ADVERSE EFFECTS IN A TERTIARY CARE HOSPITAL - T., Henry Daniel Raj; A., Sylvia; S., Chidambaranathan; P., Nirmala (International Journal of Current Pharmaceutical Research, 2017)
Objective: Epilepsy or seizure disorder is a common neurologic disorder in the pediatric age group and occurs with a frequency of 4-6 cases per thousand children. Epilepsy, particularly childhood epilepsy, remains a challenge to treat. The management of epilepsy is primarily based on theuse of anti-epileptic drugs. Surgery and diet therapy are the other modes of treating childhood seizures. To get an insight into the utilization pattern of anti-epileptic drugs (AEDs) used in pediatric seizures. Methods: This prospective, longitudinal study was conducted for a period of 8months in Paediatric Neurology Department of a tertiary care teaching hospital. The data collected from 50 children at the end of the study, were compiled in a specially designed data form and were analyzed. Results: The distribution of paediatric seizures was found to be high in male children (62%) and in the age group of 2 to 5 y (46%). The majority of the children (70%) were diagnosed with Generalized Tonic-clonic seizures. Sodium valproate was the commonly prescribed AED in all forms of seizures followed by Carbamazepine (18%), Phenobarbitone (4%) and Phenytoin Sodium (4%). AEDs were mostly prescribed as monotherapy (82%). Adverse reactions noted during this study was minimal (12%). Conclusion: Sodium valproate, a conventional AED still remains the commonly prescribed AED for all types of seizures in children aged 2 to 16 y and also was found to be effective and safe.